Professional responsibility, accountability and performativity among teachers: the leavening influence of CPD? - Sugrue, Ciaran; Mertkan, Sefika (Routledge Journals, Taylor & Francis Ltd, 2017)
In a climate of accountability and performativity, do teachers experience CPD provision as an externally imposed demand for conformity, compliance, to be accountable, or as a personal and professional rejuvenation that enhances their sense of professional responsibility? Through a qualitative study of secondary schools in England, this paper critically scrutinises the experiences of teachers in five case study schools to create a composite picture of the realities of their lives as they are buffeted and shaped by performativity while also examining the extent to which their CPD experiences may be perceived as enhancing their sense of professional responsibility. Critical analysis of the evidence suggests that the language of accountability is pervasive, and its logic gains currency by being imposed throughout schools where there is limited space to craft an alternative, thus performativity and conformity are more likely than dissent while enhancement of a sense of professional responsibility is rendered more difficult, marginalised if not entirely silenced. The concluding discussion raises critical questions regarding the health of the profession from a policy and practice perspective if the language of professional responsibility continues to be weakened or diluted by being filtered through the closely woven weave of externally prescribed accountability criteria. It concludes that the language and logic of professional responsibility is vitally necessary in provoking alternative discourses on the future of the profession and the quality of teaching, learning and leading in schools within and beyond the confines of the study.
Keywords: Accountability; performativity; professional responsibility; CPD; leadership; language and logic